Exploration of Identification at Each Phase to Advance Productivity Towards Sustainable Practices - Putri, Azhahra Divia; Putra, I Nyoman Dita Pahang; Adibah Nurul Yunisya (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
This study analyzes the productivity of tower cranes in high-rise building construction projects in Indonesia, focusing on sustainable practices and advanced techniques. The rapid growth of infrastructure has heightened competition in the construction sector, making efficiency essential. Tower cranes are key to accelerating project timelines and reducing costs, but their productivity can differ between theoretical specifications and actual field conditions. Using a quantitative descriptive method, this study compares theoretical productivity based on equipment specifications with direct field observations of the Potain MCT 205 tower crane at a high-rise site. Data on cycle time and lifting volume for work such as column reinforcement and concrete pouring were collected. Results show that theoretical productivity is higher than field observations, with a 40% increase for works and up to a 92% increase per phase. The findings stress the importance of incorporating advanced planning and sustainable practices to optimize productivity, minimize delays, and reduce costs in construction projects